A convenient synthesis of deuterium labeled amines and nitrogen heterocycles with KOt-Bu/DMSO-d6. Issue 9 (4th March 2015) - Hu, Yu; Liang, Liang; Wei, Wen-tao; Sun, Xiang; Zhang, Xue-jing; Yan, Ming
Abstract: H/D exchanges of arylmethyl amines and nitrogen heterocycles were conveniently achieved with KO t -Bu/DMSO- d 6 . The method is also applicable for phenyl benzyl ethers, diarylmethanes, and alkyl arenes. These H/D exchange reactions are suggested to proceed via a free radical pathway. Graphical abstract: